2015
DOI: 10.1007/s11356-015-5114-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochar efficiency in pesticides sorption as a function of production variables—a review

Abstract: Biochar is a stabilized, carbon-rich by-product derived from pyrolysis of biomass. Recently, biochar has received extensive attentions because of its multi-functionality for agricultural and environmental applications. Biochar can contribute to sequestration of atmosphere carbon, improvement of soils quality, and mitigation of environmental contaminations. The capability of biochar for specific application is determined by its properties which are predominantly controlled by source material and pyrolysis route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 151 publications
0
36
0
2
Order By: Relevance
“…The differences of the precursor materials of those ACs (coconut shell and lignite for ORBO and DARCO ACs, respectively) lead to different structures of porosity. Upon supplementation, this nanoporous material binds tightly halogenated compounds present in soil [3335]. In addition, this structure could explain the limitation of the CLD desorption in the digestive chyme [36].…”
Section: Resultsmentioning
confidence: 99%
“…The differences of the precursor materials of those ACs (coconut shell and lignite for ORBO and DARCO ACs, respectively) lead to different structures of porosity. Upon supplementation, this nanoporous material binds tightly halogenated compounds present in soil [3335]. In addition, this structure could explain the limitation of the CLD desorption in the digestive chyme [36].…”
Section: Resultsmentioning
confidence: 99%
“…The use of pesticides is of major importance to agriculture, but their widespread occurrence and persistence in the environment can be hazardous to living organisms. It was reported that less than 1% of the total of applied pesticides reach the targets, so a high percentage of these chemicals may move off-target [2,3]. The residues of pesticides are frequently detected in various environmental matrixes, such as soil, water, air, and organism bodies [4].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The question of whether or not biochar application can reduce the efficacy of soil-applied pesticides still needs more investigation. 18 Some authors have found lower bioefficacy of herbicides after the addition of biochar to soil due to the enhancement in sorption, which reduces the amount of pesticides in the soil solution. [19][20][21] Consequently, this behavior may affect pest management control and implies a need for additional pesticide amounts which could generate new environmental risks.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Consequently, this behavior may affect pest management control and implies a need for additional pesticide amounts which could generate new environmental risks. 18 We hypothesized in this work that the efficiency governing plant growth of the two highly mobile herbicides clomazone (CMZ) and bispyribac sodium (BYP) with different mode of action and application regime 22 could be suppressed due to biochar application. Hence, the objective was to examine the effect of six biochar additions to soil made from two different wood species and prepared at three different temperatures (350, 500 and 700 ºC) to test at laboratory scale: i) the sorption-desorption behavior of the herbicides clomazone and bispyribac sodium in soils amended with biochar, ii) the influence of biochar addition on the dissipation and leaching of CMZ and BYP, and iii) how the bioefficacy of these herbicides is affected by the presence of the biochars in soil.…”
Section: Introductionmentioning
confidence: 99%